AuthBridge Research Services Pvt. Ltd. - Agarwal, Promila; Karna, Amit (London : Indian Institute of Management, Ahmedabad, 2019)
This case describes the evolution of AuthBridge, a leading Background Screening & Risk Assessment Company. AuthBridge is the brainchild of Ajay Trehan, a serial entrepreneur with strong credentials in the field. Starting with a corporate career, Trehan took the entrepreneurial plunge in mid 1990s, and after a couple of ventures in the software and outsourcing domain, pivoted into the field of providing background screening and risk assessment for hiring talent.
Originally Published InAgarwal, P., & Karna, A. (2019). AuthBridge Research Services Pvt. Ltd. IIMA/CIIE0013. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies